Meningkatkan Literasi Financial melalui Sosialisasi Kebiasaan Menabung bagi Gen Z di Desa Perkebunan Gunung Melayu - Wahyuni Adha; Ahmad Afandi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The low level of financial literacy among students, especially Generation Z, has become a serious concern that requires solutions to face the increasingly complex challenges of the modern economy. Many students still do not fully understand the importance of financial management and continue to exhibit high consumer behavior due to the lack of financial education provided from an early age. This community service activity aims to enhance students' understanding of the importance of financial literacy through the habit of saving, which can be started at a young age as a form of simple yet highly effective financial management. The methods used in this activity include interactive lectures, pocket money management simulations, group discussions, and educational quizzes designed to increase students' active participation. The results of the activity show an increase in students' awareness of the importance of saving, as well as their ability to manage personal finances in a more directed, wise, and responsible manner in everyday life. This shows that financial education based on saving habits can help students achieve better financial management in the future.